The Socio-economic and Environmental Impacts of the Robusta Coffee Processed by the Tugu Sari Village-Owned Enterprise ‘BUMDes’, Pajahan Village, Pupuan District, Tabanan Regency - SWASTAWAN, I PUTU EDI; SUDARMA, I MADE; USTRIYANA, I NYOMAN GEDE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.8, No.2, April 2019DO - 10.24843/JAA.2019.v08.i02.p03, 2019)
The Socio-economic and Environmental Impacts of the Robusta Coffee Processed by the Tugu Sari Village-Owned Enterprise ‘BUMDes’, Pajahan Village, Pupuan District, Tabanan Regency The Tugu Sari Village-Owned Enterprise ‘Badan Usaha Milik Desa (BUMDes)’ is a Robusta coffee processing enterprise run by the village. It was established to support the Village’s Original Income ‘Pendapatan Asli Daerah (PAD)’, improve the local people’s prosperity, serve the local people, improve the management of the village’s assets, and maximize and sustain the potential which the village, as the one where Robusta coffee is produced, has. This current study was intended to identify the impact of the existence of the Tugu Sari BUMDes, Pajahan Village, based on the sustainable development system. Three impacts were explored in the current study. They are the social, economic and environmental impacts. The social and environmental impacts on the existence of the BUMDes were measured through the local people’s perception, and the economic impact was measured based on the score obtained using the Keynesian economic impact. The result of the study shows that the local people’s perception of the social impact of the BUMDes was good. The economic impact was that the existence of the BUMDes could contribute to the local people’s economy based on the score obtained through the Keynesian multiplier effect, namely 1.35. The local people’s perception was not good environmentally, as the noise produced by the coffee processing machine disturbed the learning process at Elementary School 2 Pajahan. Therefore, it is suggested that the coffee processing machine should be relocated, so it would not disturb the learning process at Elementary School 2 Pajahan.